2017
DOI: 10.1016/j.brainres.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Neural signatures of language co-activation and control in bilingual spoken word comprehension

Abstract: To examine the neural signatures of language co-activation and control during bilingual spoken word comprehension, Korean-English bilinguals and English monolinguals were asked to make overt or covert semantic relatedness judgments on auditorily-presented English word pairs. In two critical conditions, participants heard word pairs consisting of an English-Korean interlingual homophone (e.g., the sound /mu:n/ means “moon” in English and “door” in Korean) as the prime and an English word as the target. In the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 67 publications
(105 reference statements)
0
13
0
Order By: Relevance
“…Verbs are also acquired early by Mandarin-speaking children compared to other languages (Tardif, 1996). The few prior studies of lexical representation in Chinese–English bilingual speakers have focused on noun retrieval in the context of semantic facilitation, neural signatures and code-switching (Chen, Bobb, Hoshino & Marian, 2017; Chen & Ng, 1989; Li, 1996; Li, Jin & Tan, 2004). The current study adds to this body of knowledge by examining theories of bilingual naming effects and the role of grammatical category among Mandarin–English bilinguals given the verb friendliness of Mandarin and the relatively limited prior research of lexical retrieval in Mandarin–English bilinguals.…”
Section: The Current Studymentioning
confidence: 99%
“…Verbs are also acquired early by Mandarin-speaking children compared to other languages (Tardif, 1996). The few prior studies of lexical representation in Chinese–English bilingual speakers have focused on noun retrieval in the context of semantic facilitation, neural signatures and code-switching (Chen, Bobb, Hoshino & Marian, 2017; Chen & Ng, 1989; Li, 1996; Li, Jin & Tan, 2004). The current study adds to this body of knowledge by examining theories of bilingual naming effects and the role of grammatical category among Mandarin–English bilinguals given the verb friendliness of Mandarin and the relatively limited prior research of lexical retrieval in Mandarin–English bilinguals.…”
Section: The Current Studymentioning
confidence: 99%
“…Findings of cross-language activation in the bilingual lexical processing literature have been reported for different language combinations (Canseco-Gonzalez et al 2010;Ju and Luce 2004;Marian and Spivey 2003a;Pivneva et al 2014;Spivey and Marian 1999;Weber and Cutler 2004). Factors such as whether the task is conducted in the L1 or the L2 (i.e., Marian and Spivey 2003a), how proficient bilingual listeners are in the L2 (e.g., Mishra and Singh 2016;Silverberg and Samuel 2004), whether the input and bilingual listeners' lexical representation closely match (Ju and Luce 2004), daily exposure to the language (Chen et al 2017), and whether bilingual listeners expect to hear only one or both of their languages (Grosjean 1997;Marian and Spivey 2003a) have been reported to modulate the size of this cross-language activation. Of particular importance for this study could be the amount of exposure to the language between the two groups of bilinguals tested.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors have been proposed to modulate the level of cross-language activation discussed in the bilingual language comprehension literature, among which language proficiency or language dominance and language bias (or language mode) have been consistently reported (e.g., Grosjean 1997;Guo and Peng 2006;Ju and Luce 2004;Marian and Spivey 2003a;Soares and Grosjean 1984;Spivey and Marian 1999;Weber and Cutler 2004). Recently, other factors, such as daily exposure to the language (Chen et al 2017), have also been reported. However, even though most studies show support for these factors to be critical to the understanding of bilingual activation, there are other factors that are not so well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Noisy listening conditions are understood to qualitatively alter the dynamics of lexical competition in the native language ( McQueen and Huettig, 2012 ; Brouwer and Bradlow, 2016 ; Scharenborg et al, 2018 ) and recent perspectives on SPIN place the role of cognitive load front and center (see Peelle, 2018 , and Pichora-Fuller et al, 2016 for reviews). During bilingual word recognition, inhibitory control in particular is known to play a role in resolving cross-language competition ( Blumenfeld and Marian, 2013 ; Mercier et al, 2014 ; Chen et al, 2017 ), and it remains an open question to what extent other aspects of executive function may be involved as well ( Kroll and Bialystok, 2013 ; Antoniou, 2019 ). An alternative to the phonetically based account is therefore an executive function-based account : to the extent that comprehending speech in noise taxes the cognitive system, fewer cognitive resources may be available for managing activation of the non-target language, resulting in greater cross-language activation in noise.…”
Section: Introductionmentioning
confidence: 99%